Concept and Implementation of Murâbahah Agreements In The Sharia Banking Sector in Indonesia Perspective of Contemporary Ulama - Ghofur, Abdul; Fahmi, Muhammad Nurul; Dahlan, Ahmad; Mohammad, Che Adenan (Advances in Humanities and Contemporary Studies, 2024)
Many scholars have expressed various criticisms regarding the dominance of murabahah in sharia banking products, with many even calling Sharia banks "murabahah banks". Apart from that, the practice of murabahah in sharia banking has also undergone various modifications; some are even considered to deviate from the basic concept of murabahah in classical muamalat jurisprudence. This article will examine various examples and contexts as well as reasons for changes to the murabahah system in classical jurisprudence as applied in sharia banking practice. Apart from explaining the use of the murabahah system, it also explains the murabahah financing model in the sharia banking sector. Regarding the legal position or practical rules of murâbahah li al-âmir bi al-syir, according to current scholars, there are many differences of opinion. Some allow it, and some prohibit it. This research uses a literature review method from various publications or research articles. The results of library research are believed to have the ability to provide answers to problems that exist in society because library research is a synthesis of previous research that has been discussed by other researchers.